2014
DOI: 10.1016/j.rppneu.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Experiência clínica com omalizumab na consulta de asma grave

Abstract: The current analysis shows evidence that omalizumab is successful in improving asthma control as an add-on therapy GINA step 5 treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore, there were reductions in the clinically significant and severe clinically significant exacerbations similar to those observed in the global registry and other real-life studies in Portugal. 7,11 Clinically meaningful improvements in important outcomes (ACT TM and mini-AQLQ) together with over 90% of patients showing ≥0.5 score increase at Month 24 were also registered. These findings are comparable with another Portuguese study where there has been progress for ACT TM .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, there were reductions in the clinically significant and severe clinically significant exacerbations similar to those observed in the global registry and other real-life studies in Portugal. 7,11 Clinically meaningful improvements in important outcomes (ACT TM and mini-AQLQ) together with over 90% of patients showing ≥0.5 score increase at Month 24 were also registered. These findings are comparable with another Portuguese study where there has been progress for ACT TM .…”
Section: Discussionmentioning
confidence: 93%
“…Our study ( n = 465) is the second-largest after the “France real-life study” [21] ( n = 767) of the studies presenting real-life data from a single country, and the only one to present the results of 5 years of follow-up. Previous studies have mostly covered a period of ≤3 years [11-23, 25]; 1 other study presents 4-year data [24]. We consider that our study presents long-term data with an adequate number of patients.…”
Section: Discussionmentioning
confidence: 95%
“…The rates of decrease were 72, 64, and 55% for years 1, 3, and 5, respectively. Other real-life studies have reported 1st year decrease rates of 45.7% [25] and 80% [13, 15]. There are no studies to directly compare our year 3 and year 5 results, but the closest are a year 2 result of 73.2% [27] and a year 4 result of 70% [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation